The hydrogen molecule under the reaction microscope: single photon double ionization at maximum cross section and threshold (doubly differential cross sections). (24th July 2017) - Weber, Thorsten; Foucar, Lutz; Jahnke, Till; Schoeffler, Markus; Schmidt, Lothar; Prior, Michael; Doerner, Reinhard
Abstract: We studied the photo double ionization of hydrogen molecules in the threshold region (50 eV) and the complete photo fragmentation of deuterium molecules at maximum cross section (75 eV) with single photons (linearly polarized) from the Advanced Light Source, using the reaction microscope imaging technique. The 3D-momentum vectors of two recoiling ions and up to two electrons were measured in coincidence. We present the kinetic energy sharing between the electrons and ions, the relative electron momenta, the azimuthal and polar angular distributions of the electrons in the body-fixed frame. We also present the dependency of the kinetic energy release in the Coulomb explosion of the two nuclei on the electron emission patterns. We find that the electronic emission in the body-fixed frame is strongly influenced by the orientation of the molecular axis to the polarization vector and the internuclear distance as well as the electronic energy sharing. Traces of a possible breakdown of the Born–Oppenheimer approximation are observed near threshold.